Estrategias metacognitivas de un grupo de estudiantes brasileños en actividades de modelación matemática - Velozo de Castro, Élida Maiara; Almeida, Lourdes Maria Werle (Universidad de Costa Rica, 2023)
The article aims to investigate the potential of mathematical modelling to promote metacognitive strategies. The investigation, of a qualitative nature, is based on a theoretical framework and considers data obtained from students of a Mathematics Degree, at a Brazilian university, during the years 2020 and 2021. The results indicate that these strategies are triggered by the demands of the different phases of a modelling activity, that are characterized as: interaction, mathematization, resolution, interpretation and validation; preparation of a report and communication of results. Although metacognition is a personal attribute, it has manifested itself through both individual and collaborative strategies. The activities were carried out in two different moments of familiarization of the students with the modelling and, although there were no differences in the amount, there are indications that in the activity of the third moment strategies emerged that may have contributed more to the performance of the group regarding the competence to do modelling as well as for their mathematical performance. The identification of metacognitive strategies promoted by the demands of the activities leads to the conclusion that in the circumstances in which they were developed, they constitute an example of a metacognitively rich environment.